Case report: a boy with an inability to walk; do not forget about scurvy - Mansor, Noor Emilia Emira; Said, Abdul Hadi (Academy of Family Physicians of Malaysia, 2024)
Scurvy, a condition caused by vitamin C de ciency, is characterized by a syndrome of multisystem disorder due to defective collagen production and antioxidative function. is condition is infrequent in this modern era; thus, it is often not within the list of di erential diagnoses. e broad clinical picture is generally overlooked as other systemic illnesses, resulting in an extensive investigation that delays the diagnosis. Herein, we report a case of an 8-year-old boy with underlying autism spectrum disorder who presented with lower limb pain and other constitutional symptoms. Examination revealed multiple hyperpigmented scars over the upper and lower limbs and gingival hyperpigmentation. With history of picky eating habits and clinical symptoms supported by radiographic ndings, scurvy was suspected and subsequently con rmed based on a low level of ascorbic acid. With vitamin C supplementation and proper nutritional support, the patient recovered well